O Papel do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba, Campus Campina Grande, para o desenvolvimento regional - Oliveira, Ana Maria Gomes Galdino de (2019)
Through the n. 11.892/2008 Law, there was a reorganization and institution of the Rede Federal de Educação Profissional, Científica e Tecnológica and the Institutos Federais process and the Institutos Federais are part of this historical structure of expansion and internalization of professional education in the country, rewarding a social function in vocational exercise and in the pursuit of an accompanying egalitarian nation plan. Hence, this study aims to investigate the contribution of the Instituto Federal de Educação, Ciência e Tecnologia da Paraíba, Campina Grande campus, for regional development, based on its extension and culture actions. We present a historical approach concerning the expansion and internalization of the Rede Federal de Educação Profissional, Científica e Tecnológica focusing on the national and local scenario in the regional context and we show the Institutos Federais and their relationship with local and regional development. We base the research based on the authors contributions, especially Clélio Campolina Diniz and Danilo Jorge Vieira (2015), who discuss the regional development theme, presenting analyzes and discussions about the object on image. It is a field, bibliographical and documentary research that has a qualitative focus, although it is also used quantitative subsidies, with exploratory characteristics, having in the content analysis the fundamentals for the interpretation of data. Data collection was done through documentary research, as well as interviews and questionnaires applied to the research subjects. We verified that the actions of extension and culture, by promoting the interaction between the Instituto Federal de Educação, Ciência e Tecnologia, campus Campina Grande, and the society, reveal aspects suitable to contribute, for the regional development, through the extensionists programs target audience. These contributions of more subjective characteristics are inextricably related to teaching and research, not only directed to economic aspects but, most of all, to the social, cultural and environmental fields